Gincana lúdica com elementos da comunicação não violenta na educação física escolar: aprendizagens decorrentes - Trovo, Cássia de Souza (2025)
Indiscipline and aggression have negatively impacted the school environment, also affecting the Physical Education curriculum. This study aimed to describe and analyze the development of a didactic unit on Games and Play in Physical Education classes, organized as a playful activity in the form of a challenge, integrated with elements of Nonviolent Communication (NVC). The research, which adopted a qualitative approach, involved a pedagogical intervention with a 4th-grade class in a public school within the municipal system of Ribeirão Preto-SP, with the participation of 25 students in 10 lessons, each lasting 50 minutes. Data were collected through Field Notes, which were then analyzed using coding categories. The identified categories were: A) Challenges: Issues such as the presence of students from other classes in the gymnasium and resistance to NVC hindered the development of a collaborative environment, highlighting the need for ongoing strategies to support lesson development and the achievement of educational goals; B) Advances: The playful activity in the form of a challenge fostered progress, including the development of active listening, collective problem-solving, and respect for individual limitations, thereby strengthening collaboration and trust. Emphasizing the process rather than the outcome contributed to the creation of a more inclusive environment. Indiscipline and aggression have negatively impacted the school environment, also affecting the Physical Education curriculum. This study aimed to explore how the development of a teaching unit on Games and Play, organized as a playful activity in the form of a challenge, integrated with the principles of Nonviolent Communication (NVC), could contribute to a more collaborative and respectful school environment. The research, which adopted a qualitative approach, involved a pedagogical intervention with a 4th-grade class in a public school within the municipal system of Ribeirão Preto-SP, with the participation of 25 students in 10 lessons, each lasting 50 minutes. Data were collected through Field Notes, which were then analyzed using coding categories. The identified categories were: A) Challenges: Issues such as the presence of students from other classes in the gymnasium and resistance to NVC hindered the development of a collaborative environment, highlighting the need for ongoing strategies to support lesson development and the achievement of educational goals; B) Advances: The playful activity in the form of a challenge fostered progress, including the development of active listening, collective problem-solving, and respect for individual limitations, thereby strengthening collaboration and trust. Emphasizing the process rather than the outcome contributed to the creation of a more inclusive environment. Despite the challenges encountered, organizing the playful activity from a perspective that values relationships over competitiveness proved to be a promising path for transforming interpersonal relationships and fostering a more harmonious and welcoming school environment.